Development of novel bioelectrocatalytic platform based on in situ generated gold nanoparticles for biomedical applications - Pandey P.C.; Chauhan D.S. (My University, 2025)
Gold nanoparticles (AuNp) formed using alkoxysilane precursors are utilized in the development of thin organically modified silicates (ormosil) films. The resulting films are optically transparent thereby retaining the optical properties of AuNp. Surface morphology shows that the in situ generated AuNp retained their nanogeometry in the ormosil films. An application of the AuNp encapsulated ormosils is shown in electrocatalytic determination of hydrogen peroxide. For this purpose, potassium fenicyanide is chosen as electron transfer mediator and is encapsulated in the films. Results show that the presence of AuNp in the ormosil matrix dramatically improves the electrochemical behavior of potassium fenicyanide. The ormosil films are utilized for electrocatalytic determination of hydrogen peroxide. In order to investigate the biocompatibility of the ormosil film, horseradish peroxidase (HRP) is incorporated resulting in improvement in oxidation and reduction of peroxide. © 2012 Materials Research Society.